The influence of organization learning, organization commitment and internal marketing on patient satisfaction: A case at Poliklinik Eksekutif USM / Sara Aiffa Mohamad A‟Idil - Mohamad A‟Idil, Sara Aiffa (2016)
Introduction: The learning organization, organization's commitment and internal marketing are important elements to achieve patient satisfaction. In order to satisfy patients, Poliklinik Eksekutif USM‟s staffs must continually advance their competence through ongoing learning, they must feel committed to their work task so it will hold an emotional attached to their job and a good internal marketing. These factors could complement the successfulness of Poliklinik Eksekutif USM services which turn to patient satisfaction. Objective: The objective of the study was to investigate the extent to which the learning organization, organization‟s commitment and internal marketing of Poliklinik Eksekutif USM influence their patient satisfaction. Methodology: Two sets of questionnaire were developed to examine all the variables studied. The first set was distributed to 50 Poliklinik Eksekutif USM‟s staffs which asked about dependent variables (learning organization, organization commitment and internal marketing). The second sets of questionnaire were distributed to 50 patients. The questionnaire asked about their satisfaction toward Poliklinik Eksekutif USM services. Only 86 questionnaires were returned. SPSS analysis was used to evaluate the dependent variables toward patient satisfaction. Result: The finding indicated that learning organization and organization‟s commitment were statistically significant elements which contributed to patient satisfaction. Whereas, internal marketing was not a contributing factor for patient satisfaction. Conclusion: The Poliklinik Eksekutif USM‟s should emphasize more on learning organization and the organization commitment because it influenced patient satisfaction. Patient satisfaction can be improved if the staffs understand about learning organization and organization commitment, hence it can foster Poliklinik Eksekutif USM services